Dimming the “Halo” Around Monogamy: Re-assessing Stigma Surrounding Consensually Non-monogamous Romantic Relationships as a Function of Personal Relationship Orientation - Balzarini, Rhonda N.; Shumlich, Erin J.; Kohut, Taylor; Campbell, Lorne (Frontiers in Psychology, 2018)
Conley and colleagues (2013) reported that both monogamous and consensually non-monogamous participants viewed monogamous relationships more positively. However, this pattern of stigma towards consensually non-monogamous relationships and the “halo effect” surrounding monogamous relationships is at odds with the view that people typically favor members from their own groups over members of other groups. In the current research, we sought to re-examine the halo effect, using a more direct measure of stigma (i.e., desired social distance), in a methodological context that differentiates between the three most common types of consensually non-monogamous relationships. A convenience sample (N = 641) of individuals who self-identified as monogamous (n = 447), open (n = 80), polyamorous (n = 62), or swinger (n = 52) provided social distance ratings in response to these same relationship orientations in a counterbalanced order. Congruent with prior findings consensually non-monogamous participants favored monogamy over consensually non-monogamous relationships (replicating the halo effect). However, results indicated this effect dissipated when participants were asked to differentiate between relationships they identify with, and other consensually non-monogamous relationships. Furthermore, supplementary findings suggest that monogamous relationships were perceived to be the least promiscuous and were associated with the lowest perceived sexually transmitted infection (STI) rates, while swingers were perceived as the most promiscuous and were associated with the highest perceived STI rates. Consequently, our results imply social distance is partly attributable to the perception of STI risk, but not perceptions of promiscuity.